Appropriateness of attention and its connection with the maqam in verses from the Holy Quran - Saleh, Musab Fadhil (Al-Adab Journal, 2021)
The turning is a well-known linguistic phenomenon, it has been used in the Qur’an in many places, the turns have been taken into consideration the maqam in the Holy Qur’an for example, it moved from the addressed pronoun to the absent pronoun according to the maqam as the same is in moving from the pronoun to the apparent noun and other turns. The Holy Qur’an took care of all that. If it comes by turning in proportion, then it can be said that the maqam is a reason for turning and the turning is only to indicate the arrangement of the maqam and take into account it as a rhetorical method required by the context of the text. The research is titled (Appropriateness of attention and its connection with the maqam in verses from the Holy Quran), to show part of the importance of this linguistic and rhetorical method in the Holy Qur’an. I have reached several results in this research, including: the turning is one of the most important purposes of Quranic expression, as it is proportional to the maqam in general and it changes according to the change of place. The turning is multi-faceted in the Holy Qur’an, and it is used for more than one purpose, whether stylistic or semantic.The turning is about the context and running by it.